Mortality Effects of Mosquito Anopheles Sp. Malaria Vectors Caused by Exposure to Burning Mosquito Drugs and Male Breadfruit Mat - Debby Dijola Moniharapon; Adrien Jems Akiles Unitly; Maria Nindatu; Mechiavel Moniharapon; Veince B. Silahooy; Beatrix Belina Sikafir; Helena Djumaifin (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of mortality on Anopheles sp . vector of malaria due to exposure to mosquito coils and male breadfruit mats. This study used a completely randomized design (CRD), in which 180 Anopheles sp. divided into 3 groups with 3 replications, Anopheles sp. placed in 9 plastic cups, where each plastic contains 20 Anopheles sp larvae, then reared until they become mosquitoes in a mosquito net box. The results obtained were analyzed by Analysis of Variance (ANOVA) and continued with the Duncan test at real rate a= 0.05 using SAS software and continued with the smallest significant difference test to determine the difference in the treatment given. The results showed that the use of mosquito coils and electric mats for male breadfruit flowers had the same mortality effect, where the percentage of mortality was 100%.